Kemampuan Literasi Digital Santriwati Dalam Mengakses Informasi Digital Pada Ponpes YPMI Al-Firdaus Semarang - Jinan, Salwa Najla; Azhaari, Hasna; Wahyuni, Wahyuni; Kumala Putri, Nelsy (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
Digital literacy is a form of ability to obtain, understand and use information derived from various sources. People are faced by very rapid technological developments so they are required to sort and choose information that suits reality. Many people are hesitant about various kinds of media information so that they are not sure that the news is true or not so digital literacy is needed. This study used qualitative research, data obtained through observation, documentation and interviews. The results of research on the digital literacy skills of YPMI Al-Firdaus Semarang students can be seen from the ability to use the website and social media of pesantren.